Reality and Imagination: Two Elements of Identification of Three Characters in "Wandering Island" and "wandering Cameleer". - ابراهیم رنجبر (تاریخ ادبیات)
Simin Daneshvar's two-volume novel, Wandering Island and wandering Cameleer has at least two layers: a narrative layer and an interpretative layer. The author used artistic and symbolic language in its most precise and subtle quality and created new and varied codes. Linguistic structures, characters, situations, and scenes exhibit the greatest encoding capacity. Important characters in the novel are based on the identity of a number of author’s contemporary intellectuals. In a way that without comparing fictional characters with historical characters the novel cannot be analyzed properly. The author has expressed her historical theories by using the identity of a number of intellectuals in the creation of fictional characters. To the extent that the narrative layer of the novel is a fictional story and the interpretative layer contains the author's historical views on contemporary Iranian history between 1332 and 1357. In this article, using clues, situations, scenes, linguistic structures, and other elements and details, we have proved that Hasti, Morad and Salim are influenced by a few characteristics of several historical figures, including Al-Ahmad, Shariati, Maleki, Fardid, Bazargan and Daneshvar.